Capacitively Coupled Discharges as Photoionization Sources in an Electrode-Dielectric-Screen Assembly - Niedbalski, Jorge Julio (2003)
The influence of the dielectric material and the dependence of parameters (pressure, voltage, etc.) on the development of volumetric gas discharges as photoionization sources in a capacitively coupled (electrode-dielectric-screen) assembly were investigated. Two materials with very different permittivity values and high contrast in their hysteresis effects were tested in assemblies excited by high-voltage pulses with a rise time of about 5 ns within the range 5–11 kV. Discharges in nitrogen and neon gases were characterized in detail through the measurements of current and emitted light to establish the necessary conditions for an optimized performance (uniformity and intensity) of irradiation. A comparison between the two assemblies as to the production of phototriggered discharges within regions behind a single and a double screen subjected to a uniform electric field was performed.